Model of the planar broadband differential waveguide interferometer as a humidity sensor - Gut, Kazimierz (Photonics Letters of Poland, 2020)
The paper presents a model of the planar broadband differential waveguide interferometer. Its response to the change in thickness and refractive index of the waveguide layer due to the change in humidity is presented. The analysis was carried out for the wavelength range from 450 nm to 850 nm. The orthogonal modes TE0 and TM0, which propagate in this wavelength range, are considered. It is shown that by using light near the maximum of the system characteristic, instead of the spectrometer, the total power at the system output can be measured. Full Text: PDF References M. Kitsara, K. Misiakos, I. Raptis, and E. Makarona, "Integrated optical frequency-resolved Mach-Zehnder interferometers for label-free affinity sensing", Opt. Express 18, 8193 (2010). CrossRef K. Misiakos, I. Raptis, A. Salapatas, E. Makarona, A. Bostials, et al., "Broad-band Mach-Zehnder interferometers as high performance refractive index sensors: Theory and monolithic implementation", Opt. Express 22, 8856 (2014). CrossRef K. Misiakos, I. Raptis, E. Makarona, A. Botsialas, A. Salapatas, et al "All-silicon monolithic Mach-Zehnder interferometer as a refractive index and bio-chemical sensor", Opt. Express 22, 26803 (2014). CrossRef K. Misiakos, E. Makarona, M. Hoekman, R. Fyrogenis, K. Tukkiniemi, et al., "All-Silicon Spectrally Resolved Interferometric Circuit for Multiplexed Diagnostics: A Monolithic Lab-on-a-Chip Integrating All Active and Passive Components", ACS Photonics 6, 1694 (2019). CrossRef E. Makarona, A. Salapatas, I. Raptis, P. Petrou, S. Kakabakos, et al., "Broadband Young interferometry for simultaneous dual polarization bioanalytics", J Opt Soc Am B 34, 1691 (2017). CrossRef K. Gut, "Broad-band difference interferometer as a refractive index sensor", Opt. Express 25, 3111 (2017). CrossRef K. Gut, "Study of a Broadband Difference Interferometer Based on Low-Cost Polymer Slab Waveguides", Nanomaterials 9, 729 (2019). CrossRef W. Lukosz, "Integrated optical chemical and direct biochemical sensors", Sensor Actuat. B-Chem. 29, 37 (1995). CrossRef W. Knoll, O. Azzaroni, H. Duran, J. Kunze-Liebhäuser, K. Lau, et al. "Nanoporous thin films in optical waveguide spectroscopy for chemical analytics", Analytical and Bioanalytical Chemistry 412, 3299 (2020). CrossRef A. Bucciarellia, V. Mullonib, D. Maniglio, R.K. Pal, V.K. Yadavalli, at al., "A comparative study of the refractive index of silk protein thin films towards biomaterial based optical devices", Optical Materials 78, 407 (2018). CrossRef V.Prajzler, K. Min, S. Kim, and P. Nekvindova, "The Investigation of the Waveguiding Properties of Silk Fibroin from the Visible to Near-Infrared Spectrum", Materials 11, 112 (2018). CrossRef Q. Li, N. Qi, Y. Peng, Y. Zhange, L.Shi, et al. "Aggregation induced red shift emission of phosphorus doped carbon dots", RSC Advances 7, 178889 (2017). CrossRef P. Giovanni, Z. Yuji, N. Deboki, P. Nereus, D. Kaplan, et al. "The optical properties of regenerated silk fibroin films obtained from different sources", App. Phys. Lett. 111, 103702 (2017). CrossRef M. Procek, Z. Opilski, A. M. Maquenda, X.M. Berbel, S.Aznar-Cervantes et al., "Silk fibroin thin films for optical humidity sensing", Proceedings of SPIE 11204,1120409 (2019). CrossRef https://www.thorlabs.com/thorproduct.cfm?partnumber=M595F2 DirectLink